'"Narrative!" I can't hear that anymore'. A linguistic critique of an overstretched umbrella term in cultural and social science studies, discussed with the example of the discourse on climate change. Issue 3 (4th May 2021) - Reisigl, Martin
ABSTRACT: In cultural as well as social science studies of discourses (e.g. of discourses on climate change), the concept of narrative is used in a very broad sense – as an umbrella term that lacks analytical accuracy. From the perspective of linguistics, it seems obvious to acknowledge five elementary generic patterns. In addition to narration, linguists differentiate between argumentation, description, explication and instruction . Each of these patterns fulfils a different basic pragmatic function. This article tries to make clear and justify why it is important, both theoretically and practically, to make a distinction between these five generic patterns. It is argued and shown that narrativization tends to go hand in hand with a relief of action, historicization, potential fictionalization, subjectivization and relativization . With respect to discourses on the climate crisis, these prototypical characteristics of narratives undermine both scientific attempts to justify claims of truth relating to the existence, causes and consequences of global warming as well as practical attempts to motivate people to adopt a more sustainable lifestyle.